Socioeconomic cost-benefit-analysis of seasonal heat storages in district heating systems with industrial waste heat integration. (1st October 2018) - Moser, Simon; Mayrhofer, Julia; Schmidt, Ralf-Roman; Tichler, Robert
Abstract: Industrial waste heat is primarily available in summer months while district heating demand is greater in winter months. In order to shift heat potentials from summer to winter and thereby make the feed-in of industrial waste heat economically more attractive, the paper explores the use of waste heat with large-scale (seasonal) heat storage. This paper focuses on the case study of the industrial city of Linz (Austria), and demonstrates the advantages and disadvantages of seasonal heat storage. The interaction between the storage system with optimal cogeneration plant dispatch and industrial waste heat integration is explained. Furthermore, the most important parameters of the heat storage in order to achieve economic feasibility are highlighted. One main finding is that the number of annual cycles is crucial for a seasonal heat storage. The amortization period is computed to be about 20 years, and is shown to be extremely sensitive to changes in electricity, gas and CO2 prices. Highlights: The integration of waste heat through seasonal heat storage was investigated. The seasonal heat storage is only economic if used in multiple cycles per year. Carbon, fuel (gas) and electricity price uncertainties exaggerate investment risk. Storage's summer demand hardly increases the revenues of waste heat integration.